First-principles studies on band structure and mechanical properties of BiFeO3 ceramics under high pressure - Ramanathan Chandiramouli; Veerappan Nagarajan (Processing and Application of Ceramics, 2017)
Mechanical properties and band structure of rhombohedral BiFeO3 nanostructures were studied using density functional theory for different pressures in the range from 0 to 50GPa. The elastic constant of BiFeO3 nanoceramics was determined and different moduli were calculated for various applied pressures. The bulk (B) and shear (G) modulus show an increasing trend on applied high pressure. The findings of the present work also confirm that the hardness of BiFeO3 increases with the applied pressure. The ductility of BiFeO3 nanostructure increases upon increasing the pressure, which is confirmed from Poisson’s ratio and B/G ratio. The band structure studies were also carried out under high pressure and showed that the band gap decreases upon increase in the applied pressure.